2019
DOI: 10.1017/s1368980019002696
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the impact of sodium reduction from packaged foods on population sodium intake in US adults and children

Abstract: Objective:To simulate the impact that Na reductions in food categories that are the largest contributors to dietary Na intake would have on population Na intake from packaged foods among US adults and children.Design:24 h Dietary recall data were used. For each store-bought packaged food product reported by participants, we generated sales-weighted Na content at the median and 25th percentile using Nutrition Facts Panel data from 193 195 products purchased by US households. The impact that Na reductions would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…We analyzed every study for categorizing the studies into three major themes, i.e., barriers, enablers, and perceptions. [49,50] 2014 [51,52] 2011-2015 [53] 6348 food products [51] 501 public consumers (aged 18 years and above) [52] 5759 prepacked foods [53] [ [51][52][53] Australia 2010 [54] 2015 [55][56][57] 907 McDonald's and Subway lunchtime customers (aged 16-84 years) [54] 338 participants aged 18-65 years [55] 2559 Victorian adults aged 18-65 years [56] 479 adults aged 18-64 years [57] [ [54][55][56][57] 2014 1153 soup products [58] South Korea 2013 [59] 2014 [60] 257 females aged 25 to 49 years [59] 738 consumers aged 18 years and above [59,60] 2014 [61] 2018 [62] 104 food service personnel working at 17 worksite cafeterias aged 18 years and above [61] 312 restaurant managers and chefs [62] [ 61,62] USA 2012-2013 221 Chinese take-out restaurants [63] 2013-2014 [64] 2011-2012 [65] 450 adults aged 18 years and above [64] 2948 children aged 2-18 years and 4878 adults aged > 18 years [65] [ 64,65] Greece 2011 3609 Greek adults aged over 25 years [66] Canada 2011…”
Section: Extraction and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed every study for categorizing the studies into three major themes, i.e., barriers, enablers, and perceptions. [49,50] 2014 [51,52] 2011-2015 [53] 6348 food products [51] 501 public consumers (aged 18 years and above) [52] 5759 prepacked foods [53] [ [51][52][53] Australia 2010 [54] 2015 [55][56][57] 907 McDonald's and Subway lunchtime customers (aged 16-84 years) [54] 338 participants aged 18-65 years [55] 2559 Victorian adults aged 18-65 years [56] 479 adults aged 18-64 years [57] [ [54][55][56][57] 2014 1153 soup products [58] South Korea 2013 [59] 2014 [60] 257 females aged 25 to 49 years [59] 738 consumers aged 18 years and above [59,60] 2014 [61] 2018 [62] 104 food service personnel working at 17 worksite cafeterias aged 18 years and above [61] 312 restaurant managers and chefs [62] [ 61,62] USA 2012-2013 221 Chinese take-out restaurants [63] 2013-2014 [64] 2011-2012 [65] 450 adults aged 18 years and above [64] 2948 children aged 2-18 years and 4878 adults aged > 18 years [65] [ 64,65] Greece 2011 3609 Greek adults aged over 25 years [66] Canada 2011…”
Section: Extraction and Analysismentioning
confidence: 99%
“…The studies carried out in the USA showed that salt was added to the diet from different packaged/non-packaged foods or foods sourced from out-of-home settings. This was responsible for a total of 67-70% of the salt intake among the population [64,65]. Similarly, studies conducted in the European Union indicated that the people had a higher salt intake, wherein 75-80% of the salt intake was due to the consumption of processed foods, 10-15% of the salt was added during the cooking process or at the table, while 5-10% of the salt was naturally present in different food items.…”
Section: Dietary Salt Intake and Sourcesmentioning
confidence: 99%
“…The underlying purchasing data employed here have been used previously to understand the potential health impacts of optimizing nutrient intakes through interventions, such as salt reduction or the implementation of dietary guidelines 61,62 . Both the NielsenIQ Homescan and FoodSwitch datasets have been used in multiple prior analyses of product purchasing patterns in Australia and other jurisdictions 58,[63][64][65] .…”
Section: Discussionmentioning
confidence: 99%
“…In the US, a reduction of 25% sodium content in the top 10 food groups that contribute to sodium intake would represent an 8.7% reduction of the total sodium consumption of the adult population (45). Also, achieving the sodium targets proposed by the Food and Drug Administration could prevent or postpone 13 to 35 thousand deaths from CVD in US over the 20-year simulation period (46).…”
Section: Discussionmentioning
confidence: 99%